Diversity Science and Institutional Design. (October 2014) - Plaut, Victoria C.
Ideas about diversity and how to deal with difference—for example, to avoid race or attend to it—reside at the center of debates on how to build fair, inclusive, diverse environments. Social-psychological research in diversity science can inform policy makers about the implications of different approaches. Several key patterns emerge: (a) colorblindness sometimes produces more, not less, stereotyping and prejudice, and the opposite generally occurs for multiculturalism, though evidence is mixed; (b) avoiding race generally leads to worse outcomes in interracial interaction; (c) signals of organizational colorblindness generally predict negative outcomes, whereas organizational multiculturalism predicts positive outcomes, except that multicultural approaches can inadvertently send the message of valuing persons of color only for their group identity; (d) practices and policies that encourage colorblindness can leave discrimination undetected, relative to race-conscious approaches, but diversity programs can invoke a fairness illusion; and (e) majority group members may feel excluded or threatened by multicultural approaches to diversity. Overall, although attending to difference may be complicated, ignoring or avoiding it may not be as conducive to building fair, inclusive environments. The article discusses implications for the design of institutions in education, business, and public agencies, such as those that administer public services in housing, juvenile justice, and child protection.